Church, crown and complaint: petitions from bishops to the English crown in the fourteenth century - Phillips, Matthew (2013)
This thesis explores the interaction of bishops with both the English crown and members of late medieval society more generally by focusing on petitions and the supplicatory strategies adopted by bishops in their endeavours to secure legal remedy. Aside from revealing that bishops were often indistinguishable from lay petitioners in terms of the content of their petitions, with many of their complaints arising from their role as great landlords and tenants-in-chief rather than relating to the exercise of episcopal office, this research has also demonstrated that distinct supplicatory cultures separated the clergy from the laity. Notably, whereas petitions from lay supplicants often incorporated crown-alignment rhetoric into their petitions, thereby mirroring the language of ‘common profit’ found in common petitions, petitions from bishops reflected the supplicatory character of the clerical gravamina and presented requests for the exclusive interest of the church. As such, petitions from bishops, alongside the clerical gravamina, encapsulated a set of values, manifest through the use of language and rhetoric, which sought to assert the institutional independence of the church. Yet, despite being part of a supplicatory culture which sought to defend church autonomy and ecclesiastical jurisdictional integrity, the petitionary system in England sapped the supplicatory strength of the clergy and reduced their ability to defend their autonomy in the face of royal demands.